WOMENS PARTICIPATION IN LIVESTOCK FARMING ACTIVITIES - S. Arshad; S. Muhammad; I. Ashraf (Journal of Animal and Plant Sciences, 2013)
Women play a major role in livestock farming in Pakistan. They assume many activities relating to livestock production like feeding of animals, cure of animals, watering of animals, collection of fuel, milking, feeding, and cleaning of animal sheds. The present study focuses on the participation of rural women in different activities relating to livestock farming. A sample of 120 female respondents was selected randomly from Tehsil Jhang using multistage random sampling technique. They were interviewed through a reliable and validated interview schedule. The data collected, were processed through a computer software i.e. Statistical Package for Social Sciences (SPSS). The results show that milk processing, making and storage of dung cakes, collection of manure and caring of diseased animals, cleaning of animals’ sheds, watering of animals, making feed concentrates and feeding of livestock performed were the main activities performed by rural women. However their participation in most of the livestock management practices was medium to very low.
Keywords: Livestock farming; rural women; participation